Civil society and democracy promotion - Beichelt, Timm.; Hahn-Fuhr, Irene; Schimmelfennig, Frank; Worschech, Susann; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
With contributions from experts on democracy promotion, this volume examines civil society development and external civil society promotion in post-socialist Europe. It focuses on countries with a failed or deficient process of democratic consolidation looking at unintended consequences of external democracy promotion on civil society development.
Keywords: Political science; Political theory; Political communication; Comparative politics; Democracy; Europe -- Politics and government; Russia -- Politics and government; Political Science and International Relations; European Politics; Democracy; Russian and Post-Soviet Politics; Political Theory; Political Communication; Comparative Politics